2004
DOI: 10.1038/sj.ijir.3901057
|View full text |Cite
|
Sign up to set email alerts
|

The corporo-glans ligament: description and functional significance of a ligament connecting the corpora cavernosa to the glans penis

Abstract: The two corpora cavernosa (CC) end blindly under cover of the glans penis (GP). The method of attachment of the CC to the GP could not be traced in the literature. The current communication investigated the hypothesis of a ligamentous attachment existing between the two corporal ends and the GP. In all, 18 male cadaveric specimens were studied by direct dissection and histologically. Six were neonates and 12 adults (mean age 32.3710.6 s.d. y). After examining and photographing the connection between the CC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…When the CC is detached from the CS by blunt dissections, a distal cap of the glans is not easily divided from an apex of the CC due to firm attachments via a fibrous frame (Shafik et al. ; Hsu et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…When the CC is detached from the CS by blunt dissections, a distal cap of the glans is not easily divided from an apex of the CC due to firm attachments via a fibrous frame (Shafik et al. ; Hsu et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The fibrous sheath of the body merges the three parts as a unit during erection and penile propulsion (Tamaki, 1992). Compared with the TA of the CC, the TA of the cavernous body deep in the glans was thinner and less tough (Shafik et al, 2004). The distal ends of the two CC were embedded in one of the sockets of the GP (Goldstein et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The top of the CC is covered with glans cap (Hsieh et al, 2012;Kureel et al, 2015). The CS and the two CC are surrounded by tunica albuginea (TA) (Shafik et al, 2004). It is reported that there is connective tissue between the cavernous body and the glans of the penis, which is called the corporo-glans ligament (Shafik et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have clearly documented the macroscopic and microscopic morphological features of a central ligamentous structure penetrating the human glans penis by the course of the fossa navicularis. This structure has also been named the ‘distal ligament’ or ‘corporo‐glans ligament’ (Shafik et al., ; Hsu et al., ). To my knowledge, Dr Friedrich Gustav Jacob Henle (1809–1885) was first to describe this median fibrous tissue coming from the corpus spongiosum surrounding the fossa navicularis as ‘septum glandis’, and its extensions as ‘upper and lower median septum’ (Henle, ; Fig.…”
mentioning
confidence: 99%